Laccases for enzymatic colouration of unbleached cotton - Kim, Suyeon (2007)
The concept presented in this paper is the utilisation of the natural flavonoids present in cotton as anchors to attach other phenolic compounds to the fiber surface. Laccase can catalyze the oxidation of flavonoids in solution producing quinones that can be further polymerised and grafted onto surface of the cotton providing yellow to brown colouration, depending on the external flavonoids used and on the reaction conditions. Factors such as temperature, time of reaction, pretreatment of cotton, mechanical agitation and the role of an organic solvent were studied in order to improve this laccase colouration reaction. After dyeing, colour measurements and fastness tests (washing, friction and weathering fastness) were performed. A strong mechanical agitation, an increased reaction temperature (from 30 to 50 °C), and the addition of an organic solvent improved dyeing. The natural flavonoids present on cotton were found to play an important role on the grafting reaction, improving dyeing and colour fastness. Since the traditional bleaching pretreatment of cotton removes these natural flavonoids from cotton, the proposed laccase colouration reaction could be carried out without a previous bleaching treatment resulting in a more environmentally friendly process.